PERBEDAAN BERKUMUR LARUTAN DAUN KEMANGI (OCIMUM BASILICUM L) DENGAN DAUN SIRIH (PIPER BETLE L) TERHADAP PENURUNAN AKUMULASI PLAK SKOR - Misna Safitri; Naning KU Naning; Sri Nuryati (Poltekkes Kemenkes Banjarmasin, 2021)
Dental and oral diseases increase every year, especially dental caries, one of the dental and oral health problems that are often found, especially in school-age children. Plaque is a major cause of dental and oral disease, consisting of a collection of bacteria that is attached to an intracellular matrix, can be reduced by mouthwash that contains antibacterial. Antibacterial on basil (Ocimum Basilicum) and betel leaf (Piper Betle L) in the form of compounds from essential oils namely 1,8-cineole, ß-bisabolene and methyl eugenol, all of which have soluble properties to ethanol and can cause damage to bacterial cell membranes so that resulting in bacterial death. The study design is a literature study (often also called literature review) with the type of research used is descriptive. Data collection uses secondary data obtained indirectly but obtained through other people or parties, for example documents, books, research journals, scientific articles and magazines whose contents are still related to the research conducted. The results showed a significant decrease and it can be concluded that p <α means that there is a significant difference between groups that rinse the basil leaves and betel leaves to reduce plaque accumulation. The conclusions from this study indicate that there is a difference between rinses of basil leaves and betel leaves to reduce plaque score accumulation